2020
DOI: 10.1177/1076029620935201
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Vitronectin Predicts Liver Injury and Mortality in Children With Sepsis: A Prospective Observational Study

Abstract: Vitronectin (VTN) is a key regulator of coagulation, but clinical relevance of serum VTN in pediatric sepsis remains poorly defined. The aim of this study was to access the value of serum VTN level on pediatric intensive care unit (PICU) admission in children with sepsis. Pediatric patients with sepsis were enrolled from January 2018 to December 2018. The serum VTN levels were determined on PICU admission, and the association of serum VTN level with PICU mortality and organ dysfunction was assessed. Serum VTN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…Our meta-analysis provides strong support for greater organ dysfunction in nonsurvivors compared with survivors as shown by the pooled estimates for renal dysfunction (50, 64, 67, 70), multi-organ dysfunction (MODS) (23, 33, 41, 50, 69, 70, 93, 94), number of organ dysfunctions (28, 40, 64, 83), PEdiatric Logistic Organ Dysfunction (PELOD) score (23, 28, 40, 44, 50, 53, 55, 60, 65, 72, 85), and PELOD-2 (85, 86, 95). Our meta-analysis also provides strong support for greater illness severity in nonsurvivors compared with survivors as shown by the pooled estimates pediatric Sequential (Sepsis-related) Organ Failure Assessment (pSOFA) (50, 58, 70, 95) and Sequential (Sepsis-related) Organ Failure Assessment (SOFA) (85, 86, 95), PRISM (32, 43, 51, 53, 55, 60–62, 64, 68, 70–72, 75, 77, 81, 84, 85, 88), Pediatric Index of Mortality (PIM)-2 (79, 85), and PIM-3 (23, 61, 65, 85) (Supplementary Fig.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…Our meta-analysis provides strong support for greater organ dysfunction in nonsurvivors compared with survivors as shown by the pooled estimates for renal dysfunction (50, 64, 67, 70), multi-organ dysfunction (MODS) (23, 33, 41, 50, 69, 70, 93, 94), number of organ dysfunctions (28, 40, 64, 83), PEdiatric Logistic Organ Dysfunction (PELOD) score (23, 28, 40, 44, 50, 53, 55, 60, 65, 72, 85), and PELOD-2 (85, 86, 95). Our meta-analysis also provides strong support for greater illness severity in nonsurvivors compared with survivors as shown by the pooled estimates pediatric Sequential (Sepsis-related) Organ Failure Assessment (pSOFA) (50, 58, 70, 95) and Sequential (Sepsis-related) Organ Failure Assessment (SOFA) (85, 86, 95), PRISM (32, 43, 51, 53, 55, 60–62, 64, 68, 70–72, 75, 77, 81, 84, 85, 88), Pediatric Index of Mortality (PIM)-2 (79, 85), and PIM-3 (23, 61, 65, 85) (Supplementary Fig.…”
Section: Resultssupporting
confidence: 54%
“…Our meta-analysis provides strong support for greater organ dysfunction in nonsurvivors compared with survivors as shown by the pooled estimates for renal dysfunction (50,64,67,70), multi-organ dysfunction (MODS) (23,33,41,50,69,70,93,94), number of organ dysfunctions (28,40,64,83) (96) and sepsis (97), respectively. One study of children presenting to the ED with suspected infection found that a lactate level of greater than 3 mmol/L was associated with higher risk of sepsis (98).…”
Section: Organ Dysfunction Measures and Illness Severity Scoresmentioning
confidence: 54%
See 1 more Smart Citation
“…Apoa2 and Apoa4 were important apoproteins, mainly involved in the synthesis of high-density lipoprotein, which could protect blood vessels and prevent atherosclerotic diseases such as cerebral thrombosis and coronary heart disease. , A proteomic study of 141 patients with sepsis indicated that serpinf1 was highly associated with organ dysfunction and Serpinc1 was highly associated with mortality . Vtn was a key regulator of coagulation, serum VTN level was associated with sepsis-associated acute liver injury and pediatric intensive care unit (PICU) mortality, and VTN plus PRISM III was a powerful predictor of PICU mortality in pediatric patients with sepsis . Fgb played a key role in coagulation and inflammation, which also associated with mortality and organ dysfunction of patients with sepsis .…”
Section: Discussionmentioning
confidence: 99%
“…Blood Vn functions as biological "superglue": through binding to complement, heparin, and thrombin-antithrombin III complexes, this protein is in fact involved in regulation of clot formation, playing a fundamental role as a key controller of mammalian tissue repair [17]. Importantly, this aspect spills over in case of sepsis, a condition associated to highest mortality rates for patients in intensive care units [18]. At a pathological level, the main event that triggers microvascular thrombosis and multi-organ dysfunction till death during sepsis is the uncontrolled activation of the coagulation cascade [19].…”
Section: Pseudomonas Aeruginosa (Lpd)mentioning
confidence: 99%